If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d + 3 = 3d + -4 Reorder the terms: 3 + 2d = 3d + -4 Reorder the terms: 3 + 2d = -4 + 3d Solving 3 + 2d = -4 + 3d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-3d' to each side of the equation. 3 + 2d + -3d = -4 + 3d + -3d Combine like terms: 2d + -3d = -1d 3 + -1d = -4 + 3d + -3d Combine like terms: 3d + -3d = 0 3 + -1d = -4 + 0 3 + -1d = -4 Add '-3' to each side of the equation. 3 + -3 + -1d = -4 + -3 Combine like terms: 3 + -3 = 0 0 + -1d = -4 + -3 -1d = -4 + -3 Combine like terms: -4 + -3 = -7 -1d = -7 Divide each side by '-1'. d = 7 Simplifying d = 7
| 10-6x-3=2(-3-3) | | 5.2+1.2n=1.84 | | 10u=54+u | | 2(-2)-3+(-2)+1= | | 2x-20=3x+6 | | 0.5x+x=169 | | -3/7(-40-2) | | Cos(x)=0.018 | | 18=-3/7(x-2) | | 3(2x-5y)=z | | -5(8r+3)=-5(7r-5) | | 1(8+x)=7 | | 6c+11=2c+51 | | .5(x+8)=-5 | | 6-22(x+6)=2 | | 4x-7(-7-9)=42 | | 6(3+3m)=3(3m+3) | | x^2-8x=-102 | | 6b+9=5b+17 | | 2.5(6x-4)=10+(1.5+0.5x) | | -7+13=4+n | | (0-6)(2x+1)=0 | | 10a-3=6a+33 | | 16=2(x-1)-6 | | 5a^2-9ab+8a= | | .30x+.50= | | -4.5=5x-x-x | | .30x+.5= | | -10(s+4)=-62 | | 2x+2=11x-70 | | 32+2+2=3.2 | | 2(f-1)=-4 |